PENGARUH GAYA KEPEMIMPINAN, TEAM WORK, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. CUN MOTOR PONOROGO - Yoshe Anggianinda Apriani; Heri Wijayanto; Wahna Widhianingrum (Gapenas Publisher, 2022)
Human Resources is an activity to achieve success in an organization/company. To achieve the goals, targets and the ability to face various challenges, it requires adequate quality of human resources. This study aims to determine the effect of Leadership Style, Team Work, and Compensation on employee performance at PT. Cun Motor Ponorogo. The sample used in this study were 60 respondents who were employees of PT. Cun Motor Ponorogo. The testing stages used include instrument testing, coefficient of determination test, and hypothesis testing. The analysis used in this study is multiple linear regression analysis using the SPSS program. This study resulted in a partial test (t) as follows: Leadership Style (X1) = 0.002, Team Work (X2) = 0.047, and Compensation (X3) = 0.000